Allele specific expression of Dof genes responding to hormones and abiotic stresses in sugarcane - Cai, Mingxing (PLoS One, 2020)
Dof transcription factors plant-specific and associates with growth and development in plants. We conducted comprehensive and systematic analyses of Dof transcription factors in sugarcane, and identified 29 SsDof transcription factors in sugarcane genome. Those SsDof genes were divided into five groups, with similar gene structures and conserved motifs within the same groups. Segmental duplications are predominant in the evolution of Dof in sugarcane. Cis-element analysis suggested that the functions of SsDofs were involved in growth and development, hormones and abiotic stresses responses in sugarcane. Expression patterns indicated that SsDof7, SsDof23 and SsDof24 had a comparatively high expression in all detected tissues, indicating these genes are crucial in sugarcane growth and development. Moreover, we examined the transcription levels of SsDofs under four plant hormone treatments, SsDof7-3 and SsDof7-4 were down-regulated after ABA treatment, while SsDof7-1 and SsDof7-2 were induced after the same treatment, indicating different alleles may play different roles in response to plant hormones. We also analyzed SsDofs’ expression profiling under four abiotic stresses, SsDof5 and SsDof28 significantly responded to these four stresses, indicating they are associate with abiotic stresses responses. Collectively, our results yielded allele specific expression of Dof genes responding to hormones and abiotic stresses in sugarcane, and their cis-elements could be crucial for sugarcane improvement.